1994
DOI: 10.1161/01.atv.14.1.85
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypercholesterolemia in China. Identification of mutations in the LDL-receptor gene that result in a receptor-negative phenotype.

Abstract: Familial hypercholesterolemia (FH), caused by many different mutations in the low-density lipoprotein (LDL)-receptor gene, invariably leads to severe premature coronary heart disease (CHD) in homozygous individuals. Heterozygous FH patients are less severely affected but are still at increased risk of CHD in most populations. Although FH homozygotes in China are affected similarly to those elsewhere, heterozygotes are not detected in the general population and obligate heterozygotes are often not hypercholeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
2
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 28 publications
5
81
2
1
Order By: Relevance
“…Reviewing previous LDL-receptor gene sequencing data, we noted that the same heterozygous base substitution was present in the genomic DNA of a Chinese homozygous FH patient in whom we believed we had not detected any defect in the LDL-receptor gene (subject no. 1 described by Sun et al [16]). No cells were available to us from this Chinese patient, and at that time we had failed to note that the nucleotide substitution might introduce a splice site and had dismissed it as a rare silent polymorphism.…”
Section: Resultsmentioning
confidence: 99%
“…Reviewing previous LDL-receptor gene sequencing data, we noted that the same heterozygous base substitution was present in the genomic DNA of a Chinese homozygous FH patient in whom we believed we had not detected any defect in the LDL-receptor gene (subject no. 1 described by Sun et al [16]). No cells were available to us from this Chinese patient, and at that time we had failed to note that the nucleotide substitution might introduce a splice site and had dismissed it as a rare silent polymorphism.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen FH heterozygotes residing in China were recruited from family studies of Chinese homozygous FH subjects as described in detail elsewhere. 5 Canadian Chinese normolipidemic control subjects consisted of 30 non-FH subjects recruited from family studies of Chinese FH families in Vancouver. Six of these individuals were from three of the FH families discussed in this article.…”
Section: Study Subjectsmentioning
confidence: 99%
“…1 On the other hand, we have shown that individuals heterozygous for mutations in the LDLR gene who are living in China do not have a markedly elevated concentration of LDL in plasma, do not exhibit evidence of tendon or skin xanthomata, and apparently do not have any increased risk of CAD. 5 Indeed, Chinese individuals with heterozygous FH are recognized only by virtue of their being parents of offspring with mutations in both alleles of the LDLR gene. Unlike their heterozygous parents, the Chinese homozygous FH patients are as severely affected as those elsewhere and carry the same range of deleterious mutations in the LDLR gene as in other populations.…”
mentioning
confidence: 99%
“…This patient's TC level was >9.0 mmol/L. The pathogenicity of a leucine-to-proline mutation at the same location caused by a T>C base change was described by Sun et al, [15] using cell extracts from Chinese FH patients. As shown in supplementary Fig.…”
Section: Resultsmentioning
confidence: 61%